Juridical Analysis of the Mandatory Vaccination Program in Combating the Covid-19 Virus - Andhi Rahmaan Indra Rukaman; Tomy Michael (Eduvest - Journal of Universal Studies, 2024)
Vaccination implementation became mandatory after the issuance of Presidential Regulation no. 14 of 2021 concerning amendments to Presidential Regulation no. 99 of 2020 concerning Procurement of Vaccines and Implementation of Vaccinations in the Context of Combating the 2019 Coroiva Virus Dtsease (Covid-19) Pandemic. 14 of 2021 concerning amendments to Presidential Regulation no. 99 of 2020 concerning Procurement of Vaccines and Implementation of Vaccinations in the Context of Overcoming the Covid-19 Pandemic. this is contrary to Law No. 33 of 2014 concerning Halal Produce in Article 4. The results of the research show that the Implementation of Vaccinations is mandatory. Conflict of regulations regarding Vaccine obligations based on Presidential Regulation. In this case the Regulations President No. 14 of 2021 concerning amendments to Presidential Regulation no. 99 of 2020 concerning Procurement of Vaccines and Implementation of Vaccinations in the Context of Handling the 2019 Coroiva Virus Disease (Covid-19) Pandemic, it is the opposite, however, due to the massive spread of the Covid 19 virus plus the declaration of a health emergency, it is based on the principle of Salus populi suprema est where the safety of the people is more important. What is meant in this case is that under the threat of situations and emergencies, the safety of the people must be the most important goal, including if the rule of law must be set aside.